1994
DOI: 10.1681/asn.v491711
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the dialysis membrane on cytokine release.

Abstract: The immune response requires the coordinated release of a network of cytokines including interleukin-1 (IL-1), tumor necrosis factor (TNF), and IL-2. The potential role of the dialysis membrane on the elaboration of these cytokines by peripheral blood mononuclear cells (PBMNC) harvested from hemodialysis patients was investigated in a prospective crossover study. Eight hemodialysis patients, chronically dialyzed with a biocompatible membrane, were sequentially dialyzed for 2 wk with new cuprophane membranes (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…From studies in the nineties, when dialyzer membranes were less biocompatible and the water used for hemodialysis was of less microbiological quality than nowadays, it was suggested that interleukin-1 (IL-1), IL-6 or tumor necrosis factor (TNF) produced by peripheral blood mononuclear cells in the bloodstream were recognized as a pyrogenic signal by specific centers within the central nervous system (CNS). Such signals may induce the synthesis of prostaglandins that represent the central mediators of the coordinated response which may lead to a rise in core body temperature (28,31,32,33). IL-1 was found to be involved in both surges in body temperature and sleep induction (31).…”
Section: Effects Of Dialysis On the Sleep/wake Rhythmmentioning
confidence: 99%
See 1 more Smart Citation
“…From studies in the nineties, when dialyzer membranes were less biocompatible and the water used for hemodialysis was of less microbiological quality than nowadays, it was suggested that interleukin-1 (IL-1), IL-6 or tumor necrosis factor (TNF) produced by peripheral blood mononuclear cells in the bloodstream were recognized as a pyrogenic signal by specific centers within the central nervous system (CNS). Such signals may induce the synthesis of prostaglandins that represent the central mediators of the coordinated response which may lead to a rise in core body temperature (28,31,32,33). IL-1 was found to be involved in both surges in body temperature and sleep induction (31).…”
Section: Effects Of Dialysis On the Sleep/wake Rhythmmentioning
confidence: 99%
“…IL-1 was found to be involved in both surges in body temperature and sleep induction (31). However, a slight increase in body temperature has also been observed in patients undergoing hemodialysis with uncontaminated dialysate (33). Body temperature may also rise as a result of heat load from the dialysis bath.…”
Section: Effects Of Dialysis On the Sleep/wake Rhythmmentioning
confidence: 99%